Islam Literal sebagai Antinomi Konsep Kehidupan Berbangsa dan Beragama di Indonesia Perspektif Nurcholish Madjid - Pati Lewar, Paulus; Dore Woho Atasoge, Anselmus; Hayon Santri Animang, Efrem (Borneo Review, 2025)
Globalization is the process of forming a global order without national borders, allowing broad interactions among societies. This concept, although imported from Western civilization, is not a new phenomenon, as globalization has occurred in various civilizations, including Islam. However, in certain studies, modern globalization is often linked to Westernization, which has become one of the factors behind the emergence of Islamism. This study employs a literature review as its research method, examining various works and the thoughts of Nurcholish Madjid. The analysis aims to understand the dynamics of nationhood and religion in Indonesia in the face of Islamism. The study finds that Islamism seeks to maintain the existence of Islam against Western influence by implementing Islamic law as the primary guideline. Globally, this movement has expanded to Indonesia with the goal of altering the ideology of Pancasila and the concept of Bhineka Tunggal Ika. However, Nurcholish Madjid's perspective rejects the notion of a religious state, instead emphasizing Indonesia’s diversity and interfaith brotherhood. This study contributes to the development of social and political sciences by affirming the importance of diversity and tolerance in nation-building. Madjid’s thoughts serve as a key reference in preserving social harmony amid the challenges posed by Islamism.